2016
DOI: 10.1111/petr.12729
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after discontinuation of routine use of transanastomotic biliary stents in pediatric liver transplantation at a single site

Abstract: Routine use of transanastomotic biliary stents (RTBS) for biliary reconstruction in liver transplantation (LT) is controversial, with conflicting outcomes in adult randomized trials. Pediatric literature contains limited data. This study is a retrospective review of 99 patients who underwent first LT (2005-2014). In 2011, RTBS was discontinued at our center. This study describes biliary complications following LT with and without RTBS. 56 (56%) patients had RTBS. Median age at LT was 1.9 yr (IQR 0.7, 8.6); 55%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The majority of biliary strictures are diagnosed in the first 6 months after LT, most commonly at the site of surgical biliary reconstruction. (1,4) Previous studies of pediatric transplantation recipients have identified risk factors for biliary strictures including technical variant grafts, hepatic artery thrombosis (HAT), prolonged cold ischemia time, acute rejection, ABO blood group incompatibility, donation after circulatory death, and primary duct-to-duct biliary reconstruction. (3,(5)(6)(7) As 60% of pediatric LT candidates are under 5 years of age at time of wait listing, (8) and technical variant grafts are the mainstay to increase access to transplantation due to size restrictions, biliary strictures will continue to significantly impact the success of pediatric LT.…”
mentioning
confidence: 99%
“…The majority of biliary strictures are diagnosed in the first 6 months after LT, most commonly at the site of surgical biliary reconstruction. (1,4) Previous studies of pediatric transplantation recipients have identified risk factors for biliary strictures including technical variant grafts, hepatic artery thrombosis (HAT), prolonged cold ischemia time, acute rejection, ABO blood group incompatibility, donation after circulatory death, and primary duct-to-duct biliary reconstruction. (3,(5)(6)(7) As 60% of pediatric LT candidates are under 5 years of age at time of wait listing, (8) and technical variant grafts are the mainstay to increase access to transplantation due to size restrictions, biliary strictures will continue to significantly impact the success of pediatric LT.…”
mentioning
confidence: 99%